1999
DOI: 10.1007/s004320050257
|View full text |Cite
|
Sign up to set email alerts
|

Unique features of the okadaic acid activity class of tumor promoters

Abstract: Following the first report of tumor promotion by okadaic acid in 1988, we further identified additional tumor promoters of the okadaic acid activity class, such as calyculin A and microcystin-LR. However, tautomycin, which is also an inhibitor of protein phosphatases-1 and -2A (PP-1 and PP-2A), as are okadaic acid, calyculin A and microcystin-LR, is not a tumor promoter on mouse skin or in rat glandular stomach. This paper presents unique features of the okadaic acid activity class of tumor promoters with rega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
55
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(57 citation statements)
references
References 14 publications
1
55
0
1
Order By: Relevance
“…Among more than 60 types of MCs identified, MC-RR and LR were the dominant types of MCs worldwide (Haider et al, 2003), which have been found from fresh water bodies to oceans and shown tumor promoting activity through the inhibition of protein phosphatases (Fujiki and Suganuma, 1999). Recently, a provisional safety guideline of 1.0 lg l À1 MC-LR in drinking water was recommended by WHO (Falconer, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Among more than 60 types of MCs identified, MC-RR and LR were the dominant types of MCs worldwide (Haider et al, 2003), which have been found from fresh water bodies to oceans and shown tumor promoting activity through the inhibition of protein phosphatases (Fujiki and Suganuma, 1999). Recently, a provisional safety guideline of 1.0 lg l À1 MC-LR in drinking water was recommended by WHO (Falconer, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…18 The algal toxin okadaic acid (OA) is a potent inhibitor of a subgroup of serine/threonine phosphatases, including the two most abundant phosphatases, PP1 and PP2A, in mammalian cells. 19 ± 21 Although prolonged exposure to low concentrations of OA promotes tumour formation, 22 acute exposure of cells to moderate or high concentrations of OA invariably leads to apoptosis. 23 ± 28 OA-induced death can be both dependent and independent of gene transcription, protein synthesis, p53 expression, and caspases.…”
Section: Introductionmentioning
confidence: 99%
“…Acute intoxications with microcystins result in fulminant liver damage (Runnegar and Falconer 1982). Microcystins and nodularins have also been shown to be tumor promoters (Fujiki and Suganuma 1999).…”
mentioning
confidence: 99%